Platelets express adaptor proteins of the extrinsic apoptosis pathway and can activate caspase-8 - Goelz, Nadine (PLoS One, 2021)
BACKGROUND: Apoptotic pathways in platelets are important for their survival and function. Platelet apoptosis may be involved in the pathogenesis of immune thrombocytopenia (ITP), an autoimmune-mediated disease. In contrast to the intrinsic apoptosis pathway, not much is known about the extrinsic pathway mechanisms in platelets. OBJECTIVES: To investigate the expression of proteins involved in the extrinsic apoptosis pathway, including the death receptors, adaptor and regulator proteins in human platelets. To determine a possible trigger of the extrinsic apoptosis pathway in platelets. METHODS: To investigate the expression of key markers of the extrinsic pathway we used targeted immunofluorescence and flow cytometry assays. To study their expression and interaction we performed Western blotting and co-immunoprecipitation. Treated platelets with different apoptosis triggers were subjected to flow cytometry. RESULTS: We could identify the protein expression of the pro-apoptotic proteins TRADD (Tumor Necrosis Factor Receptor type 1- Associated DEATH Domain protein), TRAF2/5, (TNF Associated Factor) and DEDAF (Death Effector Domain- Associated Factor), FADD (Fas-Associated protein with death domain) as well as the anti-apoptotic proteins DJ-1 (Deglycase 1) and c-FLIP in human platelets. ABT-737 treatment induced a disruption in the co-localization of DJ-1 with FADD. Platelets treated with ABT-737 showed an activation in caspase-3 and -8. The exposure to TNF (Tumor Necrosis Factor), FasL (Fas ligand), and TWEAK or to plasma derived from ITP patients, did not lead to changes in caspase-3 and -8 activation in platelets. CONCLUSIONS: Human platelets express some proteins of the extrinsic apoptosis pathway which can be modulated only by ABT-737 treatment. However so far, no other apoptosis trigger or interaction with an external receptor have been yet identified.